The Effort to Improve Learning Outcomes of Squat Style Long Jump with Modification of Learning Media - Sanusi Hasibuan; Selmi Miranda Sari (Randwick International of Social Science Journal, 2022)
This study aims to determine the increase in learning outcomes of the squat style long jump with modification of learning media in fifth grade students of SD Negeri 064975 for the 2016/2017 academic year. This research method is Classroom Action Research (CAR). The research subjects were 41 people consisting of 20 sons and 21 women. The research was carried out at SD Negeri 064975 on November 23 to November 30, 2016. The data collection technique used an observation sheet and a portfolio assessment sheet. The results of the first cycle of research, from 41 students there were 22 students (54%) completed and 19 (46%) did not complete with an average score of 72.25 (incomplete). The results of the second cycle of 41 students were 36 students (88%) completed and 5 students (12%) did not complete with an average score of 80.94 (completed). The increase in the average value between cycle I and cycle II was 8.69. Based on the results of the data analysis, it can be concluded that using modified learning media can improve the learning outcomes of the squat style long jump in fifth grade students of SD Negeri 064975, Medan Denai District, Medan City, 2016/2017 Academic Year.